Single-cell RNA-seq reveals cellular hierarchies and impaired developmental trajectories in pediatric ependymoma - Gojo, Johannes; Hübner, Jens-Martin; Pajtler, Kristian Wilfried; Milde, Till; Pfister, Stefan; Kool, Marcel (Cancer cell, 2020)
Ependymoma is a heterogeneous entity of central nervous system tumors with well-established molecular groups. Here, we apply single-cell RNA sequencing to analyze ependymomas across molecular groups and anatomic locations to investigate their intratumoral heterogeneity and developmental origins. Ependymomas are composed of a cellular hierarchy initiating from undifferentiated populations, which undergo impaired differentiation toward three lineages of neuronal-glial fate specification. While prognostically favorable groups of ependymoma predominantly harbor differentiated cells, aggressive groups are enriched for undifferentiated cell populations. The delineated transcriptomic signatures correlate with patient survival and define molecular dependencies for targeted treatment approaches. Taken together, our analyses reveal a developmental hierarchy underlying ependymomas relevant to biological and clinical behavior.
Gesehen am 08.09.2020